Por uma história dos esportes californianos no Brasil: o caso da juventude skatista (1970 1990) - Brandão, Leonardo (2012)
This thesis aims to reflect on the development of so-called "California sports" and / or "extreme sports" in Brazil, taking as case study the practice of analyzing and skateboarding through a series of magazines published in the country between the 1970s and early 1990s. The starting point was the theory that the sport can be understood as a set of technical and organizational discourses of embodiment, and therefore being able to drive themselves to the most diverse forms of bodily experience (such a perspective is worked on the thesis by notion of power sports). We seek not only to investigate the different ways the skateboarding was co-opted by the sports universe, but also how he invented modes of spatial appropriation of subjectivity and experience that had little to do with competitions, ranking or income. The thesis we defend is that skateboarding is not trod the ways of a sportivization to result in a solid identity and which we could classify as sports. His practice was in an area of fluid and ambiguous boundaries, establishing dialogues with both the world of sports competitions organized as important to the counterculture youth movements, especially with punk rock. The restraints by which it passed in the mid-1970s, as he faced a ban in 1988, when former President Janio Quadros was mayor of Sao Paulo, indicate right, beside the existence of organized competition for a lot public, and sponsored by major companies such as Bank Itau, the existing imbalances in recent history